Geopolitične razsežnosti črnogorskega narodnega vprašanja - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2010)
Are the Montenegrins a nation? Despite their old statal tradition, the dominant group of Montenegro, one of the smallest European nation-states, namely Montenegrins, in many texts were treated as Serbs. On the other hand, Montenegrins have many specific characteristics that demonstrate their national individuality. In the last census in 2003, the proportion of Montenegrins dropped to just 43 per cent (in 1948 was still 92 per cent) - the lowest in the whole of Europe. But this result shows the core problem: the existence of two overlapping identities among Montenegrins, Montenegrin and Serbian. Do they really exist separately, or is this simply the result of the typically Balkan mixing of identities? The paper analyzes the Montenegrin national question and Montenegrin ethnogenesis by using three approaches: an analysis of the territorial and political development of Montenegro as well asits neighboring countries; an evaluation of the geopolitical dimensions of Montenegrin-Serbian relations; and a comparative analysis of cultural and linguistic phenomena in the region. The study is a part of much more extensiveresearch into the geopolitical dimensions of national questions and wider interethnic relations in the Balkans.
Keywords: Črna gora; Črnogorci; narodnostno vprašanje; etnična struktura; narodna identiteta; zgodovina; history